Decoupled timescales of organic carbon and phosphorus recycling in the global ocean - Megan R. Sullivan; François W. Primeau; Hojong Seo; Judith Camps-Castellà; Keisuke Inomura; Adam C. Martiny (Proceedings of the National Academy of Sciences, 2026)
The ocean’s biological carbon pump exports atmospheric CO 2 to the deep ocean, where it can remain sequestered for decades to centuries, and attempts to artificially enhance this natural carbon sink by fertilizing portions of the open ocean could help mitigate the impacts of excessive anthropogenic CO 2 emissions. However, differences in the cycling rates of carbon and other nutrients may impact the long-term response to ocean fertilization. In this study, we use a steady-state global biogeochemical inverse model, optimized to match hydrographic observations, to examine how differential production, remineralization, and circulation-driven re-exposure timescales of organic carbon and phosphorus affect long-term carbon sequestration. We partition global organic matter production based on the time required for regenerated carbon and phosphorus to return to the ocean surface. We find that less than 15% of total organic carbon and 31% of total organic phosphorus production remains sequestered in the ocean interior for ≥ 1 y, with only 3.3% (1.8 Pg C y −1 ) and 8.3% (0.046 Pg P y −1 ), respectively, remaining for a century or longer. The C:P ratio of the sequestration flux declines with increasing residence time, from 255:1 for total production to 98:1 for material sequestered for 100+ years, indicating that carbon is recycled to the surface more rapidly than phosphorus. This decoupling between carbon and phosphorus sequestration timescales could result in a “productivity hangover,” where the slow recovery of surface phosphate leads to a long-term suppression of global productivity, reducing the net removal of atmospheric CO 2 .